2012
DOI: 10.1111/j.1755-3768.2012.02498.x
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of mycophenolate mofetil therapy combined with systemic corticosteroids in acute uveitis associated with Vogt–Koyanagi–Harada disease

Abstract: . Purpose:  To study the effectiveness of mycophenolate mofetil (MMF) as first‐line therapy combined with systemic corticosteroids in acute uveitis associated with Vogt–Koyanagi–Harada (VKH) disease. The outcomes in this group were compared with those of another group of patients with VKH disease who were treated with corticosteroid monotherapy or with delayed addition of immunomodulatory therapy. Methods:  This prospective study included 19 patients (38 eyes) diagnosed with acute uveitis associated with VKH d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 34 publications
0
41
0
10
Order By: Relevance
“…2123 Some studies suggest that using immunosuppressive therapy (IMT) along with corticosteroids results in better visual outcomes compared to using corticosteroids as monotherapy or with delayed addition of immunosuppressants. 16,17 Overall, VKH studies have had varied results, and prospective studies comparing IMT are incredibly scarce. There are several drawbacks to retrospective and non-randomized prospective studies, such as indication bias.…”
Section: Introductionmentioning
confidence: 99%
“…2123 Some studies suggest that using immunosuppressive therapy (IMT) along with corticosteroids results in better visual outcomes compared to using corticosteroids as monotherapy or with delayed addition of immunosuppressants. 16,17 Overall, VKH studies have had varied results, and prospective studies comparing IMT are incredibly scarce. There are several drawbacks to retrospective and non-randomized prospective studies, such as indication bias.…”
Section: Introductionmentioning
confidence: 99%
“…Such incidence could probably be reduced by using immunomodulatory therapy to achieve better control of inflammation and reduce vision-threatening complications occurring in the chronic, recurrent phase of VKH. 16 The IOP and number of antiglaucoma medications decreased significantly throughout the follow-up period.…”
Section: Discussionmentioning
confidence: 98%
“…A topical steroid such as prednisolone acetate 1% is recommended for anterior uveitis. A prospective study of mycophenolate mofetil combined with systemic corticosteroids for acute uveitis reported statistically significantly lower recurrent inflammation and a 35% lower incidence of complications with combined therapy versus corticosteroid monotherapy 37. The authors of this study concluded that combined therapy as initial therapy reduced the recurrence of uveitis and significantly improved visual outcome 37…”
Section: Diagnosis and Management Of Specific Uveitic Emergenciesmentioning
confidence: 97%
“…The prevalence of uveitis seems to differ in different regions of the world 37. This difference is partially due to the pathogens in the region 43.…”
Section: Etiology Of Emergent Uveitis In Saudi Arabiamentioning
confidence: 99%